Wisdom in Buddhist Philosophy - Phanich, Pra Muan (Asia Pacific Journal of Religions and Cultures, 2021)
Knowledge is the requirement of the people. The path or way of knowing happens to two types. First Learning comes from learning through experience, and the senses. This kind of knowledge comes from internal and external reactions, which this is a knowledge that people can learn. Secondly, the knowledge that arises from self-training and self-training until the knowledge comes from the mental experience Which is knowledge that requires mental training Is the knowledge that is beyond the experience and senses of general knowledge and this kind of knowledge has the ultimate goal of knowing the truth or knowing the true truth that will lead to salvation.